Development of A University Innovation Ecosystem: An Analysis of International Practices, Interaction of Universities, Research Institutions, Industry, Development Institutions and Government Entities - Yelena V. SHEVCHENKO; Victor F. STUKACH; Nataliya V. ALEXANDROVA; Danil S. NIKULIN (Communications of International Proceedings, 2022)
Emergence of new challenges related to the climate change, pandemic effects, volatility of the energy and food markets hinder innovation development. In this regard the development of local competencies is becoming critical for the development of effective innovation ecosystem. Improvement of country's competitiveness can be achieved based on industrial modernization based on R&D commercialization, as well as ensuring accelerated development of breakthrough technologies, focused on society’s need and problems. To concentrate resources and increase collaboration of science, technology and innovation (STI) actors government should initiate foresight activities that help to build a common vision of the future and engage all stakeholders (research and business community, government entities, development institutions, funding agencies, etc.) to collaborate withing innovation ecosystem. The main problem of innovation ecosystem development in CIS countries is a poor link between the supported STI priorities on the state level and the real needs of business and society as well as lack of a coherent mechanism to support projects from the idea to the stage of implementation and scaling.
Keywords: Innovation Infrastructure; University Innovation Ecosystem; Research-Industry Collaboration